The light - MacHale, D. J. (MacHale, D. J. Morpheus Road., 2010)
Sixteen-year-old Marshall Seaver is expecting a boring summer when his best friend goes away, but instead he finds himself haunted--and hunted--by ghosts that want something from him which he cannot decipher.